Successful Deceased Donor Kidney Transplantation in a Highly Sensitized Patient after Reclassification of Unacceptable Antigens Based on HLA Epitope Analysis - Daniela Alfere; Sandra Tafulo; Isabel Tavares; Ana Teresa Nunes; Ana Rocha; Manuela Bustorff; Susana Sampaio (Publicações Ciência e Vida, 2022)
For patients with end stage renal disease, kidney transplant offers significant survival and quality-of-life advantages compared with dialysis. But for patients seeking transplant who are highly sensitized, waiting times have traditionally been long and options limited. We present the case of a 34-year-old hypersensitized female who underwent renal retransplantation. Histocompatibility tests revealed a calculated panel-reactive antibody of 99.53% with multiple antibodies against class I and II human leucocyte antigens and an eplet analysis was performed. The donor's potential unacceptable antigens were re-defined and the calculated panel-reactive antibody decreased to 88.38%. After one month the patient received a deceased-donor kidney transplant. Complement dependent cytotoxicity crossmatch was negative; virtual crossmatch and flow cytometry crossmatch with historical serum were positive. High-dose intravenous immunoglobulin and rituximab were added to the thymoglobulin-based induction immunosuppression. Three donor-specific antibodies were detected and plasmapheresis was performed. Renal allograft biopsy revealed no manifestations of rejection. Repeated testing observed a decrease in donor-specific antibodies median fluorescence intensity values. Four months post-transplant, the patient remained with normal graft function without proteinuria. She is receiving a standard maintenance immunosuppression regime with prednisolone, mycophenolate mofetil and tacrolimus. The careful discussion among the transplantation center and histocompatibility laboratory in association with intense immunosuppression and close laboratory monitoring allowed a successful human leukocyte antigen-incompatible deceased donor kidney transplantation in the most critical phase for the occurrence of humoral rejection. It is noteworthy that the new histocompatibility and immunogenetics methodologies provide a more affirmative and comprehensive assessment of mismatch acceptability